Analysis of Ballistic Capability in Making Bulletproof Multilayers Using Woven Ramie Fiber, Hardfacing Metal with Epoxy Matrix for Bulletproof Vests - Permana, Rizal Wahyu; Hadi, Syamsul; Dana, Bima Cahya Maula (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
Bulletproof material in level III bulletproof vests must be created using hard and soft materials to prevent bullet penetration. Kevlar and SiC + PE are imported materials used as armor in bulletproof vests. The use of Kevlar and SiC is very dependent on foreign sources with high prices. An innovation was carried out by making bulletproof material using cheaper multilayer methods involving metal from hardfacing welding as a hard layer and ramie fiber as a soft layer with an epoxy matrix. To see the level of penetration and surface morphology structure in the specimens, 9 variations were made: 3 layers of hardfacing welding and 3 epoxy volume fractions (40%, 45%, 50%). Ballistic test using NIJ 0101.06 level III standards with AK-47 of 7.62 mm x 39 mm bullets and the morphology of bulletproof multilayer material after impact was observed using SEM. The results showed all specimens failed to withstand bullet penetration at a distance of 15 meters. Meanwhile, at 50 meters, the S2-C specimen with a 60% epoxy volume fraction was able to withstand bullet penetration with a BFS value of 25.85 mm. This value is < 44 mm; thus, it complies with the NIJ 0101.06 body armor standard. According to SEM, most of the failures occurred because the resulting adhesion force was weak. It was necessary to add reinforcing material so that the adhesion force between the metal, ramie fiber, and adhesive increases; the materials must also have very light density to prevent the effectiveness reduction of the multilayer.